KETERSEDIAAN STANDAR PELAYANAN TERHADAP PENYANDANG DISABILITAS DI PENGADILAN AGAMA KABUPATEN SINJAI PERSPEKTIF SIYASAH SYAR'IYYAH - Febrianti, Syahruni (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to describe the Availability of Service Standards for Persons with Disabilities in the Sinjai Religious Court from the Siyasah Syar'iyyah Perspective. In answering these problems, the author uses a normative syar`i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the study show that the provision of service standards for persons with disabilities at the Sinjai Religious Court in the field of facilities and infrastructure has not met the predetermined service standards, because only three (3) facilities are available out of 24 facilities that must be provided by the court, the three facilities are wheelchairs, toilets and documents printed in braille. The implementation/operation of service standards for persons with disabilities at the Sinjai Religious Court did not operate properly, due to the lack of available facilities to assist persons with disabilities. In the view of siyasa syar'iyyah, service standards must provide an attitude of justice to every human being, including persons with disabilities. As in QS. Al-Hujurat verses 11-12 which explains that it is forbidden to humiliate one another. This is in accordance with Islamic law which calls on all people to love and help one another. In QS. An-Nuur verse 16 also mentions that as a Muslim are required to respect each other.